Aplikasi Sistem Informasi Perpustakaan Satuan Pendidikan Non-formal Sanggar Kegiatan Belajar Kota Palangka Raya Berbasis Web - Priskila, Ressa; Isachar, Michael (Journal of Information Technology and Computer Science, 2022)
The development of information technology in the field of education, especially in the Non-formal education unit of Palangka Raya City Learning Activities Center, requires a library information system. This library information system can increase the effectiveness and flexibility in collecting books, collecting members, and borrowing and returning books because, in the Non-formal education unit of the Palangka Raya City Learning Activities Center, things are still conventional, namely, the process of collecting books, collecting member data, and carrying out loan and return transactions is only carried out by writing on books. School libraries have a very influential role in the achievement of national education. The waterfall development method was used in the design of this information system. Where the waterfall method has six phases, namely requirement definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance, The results achieved are the availability of information systems supporting the processes of book data collection, member data collection, and book lending transactions. The existence of this web-based library information system is intended to assist librarians in managing book data, member data, and book loan and return transaction data, and this information system is also expected to facilitate students in searching for book collections available in the library.